2019
DOI: 10.1186/s12964-019-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

OMICs approaches-assisted identification of macrophages-derived MIP-1γ as the therapeutic target of botanical products TNTL in diabetic retinopathy

Abstract: Background: Inflammatory reaction in the dysfunction of retinal endotheliocytes has been considered to play a vital role in diabetic retinopathy (DR). Anti-inflammatory therapy so far gains poor outcome as DR treatment. This study aims to identify a novel therapeutic target of DR from the OMICs studies of a traditional anti-DR botanical products TNTL. Methods: Hyperglycemic mice were treated with TNTL. The anti-hyperglycemic effect of TNTL was validated to confirm the biological consistency of the herbal produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“… 4 During the development of DR, capillary nonperfusion would lead to increased pro-inflammatory factors because of retinal ischemia/hypoxia. Clear evidence from both DM animal models and clinical patients have demonstrated that inflammation plays an essential role in the pathogenesis of DR. 5 As reported in a previous study, it has been found that pro-inflammatory growth factors and cytokines, such as tumor necrosis factor alpha (TNFα), interleukin 6 (IL6), interleukin 1β (IL1β) and monocyte chemo-attractant protein-1 (MCP-1), are overexpressed in clinical samples of patients with DR. 6 Increased expression of inflammatory factors lead to BRB breakdown, and then damaged BRB is a key pathological progression in the incidence of macular edema. In a later stage of DR, angiogenesis would also be induced by the up-regulation of pro-angiogenic factors angiopoietin 2 (Ang 2) 7 and vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 85%
“… 4 During the development of DR, capillary nonperfusion would lead to increased pro-inflammatory factors because of retinal ischemia/hypoxia. Clear evidence from both DM animal models and clinical patients have demonstrated that inflammation plays an essential role in the pathogenesis of DR. 5 As reported in a previous study, it has been found that pro-inflammatory growth factors and cytokines, such as tumor necrosis factor alpha (TNFα), interleukin 6 (IL6), interleukin 1β (IL1β) and monocyte chemo-attractant protein-1 (MCP-1), are overexpressed in clinical samples of patients with DR. 6 Increased expression of inflammatory factors lead to BRB breakdown, and then damaged BRB is a key pathological progression in the incidence of macular edema. In a later stage of DR, angiogenesis would also be induced by the up-regulation of pro-angiogenic factors angiopoietin 2 (Ang 2) 7 and vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 85%
“…CSF3, COL18A1, CXCR2, CCR1, FGF23, CXCL11, and IL13 were previously reported as related to PDR pathogenesis based on a Laplacian heat diffusion algorithm [20]. Therapeutic strategies targeting MIP1γ to inhibit CCR1-related signaling in retinal endothelial cells might have potential against DR progression [21]. CCR7 significantly enhanced neovascularization and the nonperfusion area in oxygen-induced retinopathy [22].…”
Section: Discussionmentioning
confidence: 99%
“…2 People's Hospital of Nanjing Medical University (Nanjing, China). Streptozotocin (STZ)-induced hyperglycemic mice were utilized as the type I diabetic-like model associated with retinopathy, as previously described ( 20 ). Male C57/BL/J mice received constitutive intraperitoneal injections of 50 mg/kg STZ in a citric buffer (pH 4.5) once/day for 5 days.…”
Section: Methodsmentioning
confidence: 99%